Disappearing Dalit Haruwa-Charuwa labor in Tarai Agriculture: Causes and Consequences of Land Fragmentation - Ghimire, Kumar (Namuna Academic Journal, 2023)
This research is conducted in Tarai agriculture practice in Baijanathpur village of Morang District in eastern Tarai to explore why Haruwa-Charuwa labor has been disappearing from Tarai agricultural works? It is based on qualitative historical methodology; field observation, key informant and life history interview method to collect reliable and valid data from field. This study manifested the problem why Dalit labor has disappeared in agriculture and how they are getting survive without proper livelihood opportunity. It has signified to acknowledge that Tarai is changing its agriculture structure in its relation of labor disappearing from agriculture works. After the continuation of change and development in Tarai (migration, population growth, technology), agriculture could not consume enough labor power, so that, Dalit Haruwa-Charuwa labor has been facing job scarcity and livelihood problem due to causes of land fragmentation. This study provides a deeper conceptual understanding linkage between land fragmentation and consequence of farm labor declining in rural Tarai and investigates this relationship empirically.